Zadovoljstvo z življenjem pri osebah, odvisnih od alkohola - Čuček-Trifkovič, Klavdija (Obzornik zdravstvene nege, 2010)
Introduction: Alcohol dependency is the most common dependency disorder which affects individuals at health-related, economic and social levels. The articlediscusses satisfaction with onećs life - one of the key factors of quality of life - in alcohol dependant individuals prior to and after treatment of their dependency as well as their social reintegration. Methods: The descriptive method was used to analyse quantitative data collected througha Quality of Life Enjoyment and Satisfaction Questionnaire (Q-LE S-Q). The sample consisted of 210 alcohol dependant and non-dependant participants from north-eastern and south-western Slovenia, aged between 20 and 66. Their participation was voluntary and anonymous. Results: The study shows that when evaluating parameters of satisfaction with life a statistically significant difference was only revealed for the subjective evaluation of participantsć own well being and their own evaluation of their leisure activities. For all other factors of satisfaction with life, such as physical health, social relations and general activities, the difference was found to be insignificant. Discussion and conclusion: Quality of life is a complex factor which is based on peoplećs subjective experiencing of their lives. Given that dependency disorders highly influence peoplećs health as well as their functioning in their social surroundings, they consequently also affect their quality of life, which is, as shown by many domestic and foreign studies, significantly lower in alcohol dependant people than in non-dependant ones.
Keywords: Alcoholism; Alkoholizem; ankete; Attitude To Health; Kvaliteta življenja; Odnos do zdravja; odvisniki; Quality Of Life; Questionnaires; Recreation; Rekreacija; Social Environment; Socialno okolje; zadovoljstvo